2018
DOI: 10.1007/s10126-017-9789-x
|View full text |Cite
|
Sign up to set email alerts
|

The Voltage-Dependent Anion Channel (VDAC) of Pacific Oysters Crassostrea gigas Is Upaccumulated During Infection by the Ostreid Herpesvirus-1 (OsHV-1): an Indicator of the Warburg Effect

Abstract: Voltage-dependent anion channel (VDAC) is a key mitochondrial protein. VDAC drives cellular energy metabolism by controlling the influx and efflux of metabolites and ions through the mitochondrial membrane, playing a role in its permeabilization. This protein exerts a pivotal role during the white spot syndrome virus (WSSV) infection in shrimp, through its involvement in a particular metabolism that plays in favor of the virus, the Warburg effect. The Warburg effect corresponds to an atypical metabolic shift t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
(75 reference statements)
0
6
0
2
Order By: Relevance
“…Such features of the infection process appear to be shared with other viruses, such as human papillomavirus (HPV), human cytomegalovirus (HCMV; β-herpesvirus), Kaposi’s sarcoma herpesvirus (KSHV), and hepatitis C virus. 7174 These findings were recently substantiated by Delisle et al, 75 who developed a specific C gigas VDAC antibody and identified associations between VDAC abundance and virus susceptibility during field exposures.…”
Section: Dual Proteomics and Metabolomicsmentioning
confidence: 70%
“…Such features of the infection process appear to be shared with other viruses, such as human papillomavirus (HPV), human cytomegalovirus (HCMV; β-herpesvirus), Kaposi’s sarcoma herpesvirus (KSHV), and hepatitis C virus. 7174 These findings were recently substantiated by Delisle et al, 75 who developed a specific C gigas VDAC antibody and identified associations between VDAC abundance and virus susceptibility during field exposures.…”
Section: Dual Proteomics and Metabolomicsmentioning
confidence: 70%
“…Presently, a specific proteomics tool has been developed for VDAC quantification, which could be used to measure the oyster susceptibility to OsHV‐1 (Delisle et al . ). Proteomics was also used to analyse differences in susceptibility of Pacific oyster C. gigas and Sydney Rock oyster Saccostrea glomerata to the OsHV‐1 through observations in proteomic changes related to double‐strand RNA (dsRNA) (poly I:C and poly A:U) injection using isobaric tags for relative and absolute quantitation (iTRAQ) (Masood et al .…”
Section: Applications Of Proteomics In C Gigas Mortality Eventsmentioning
confidence: 97%
“…For instance, the voltage‐dependent anion channel (VDAC), which controls the influx and efflux of metabolites and ions through the mitochondrial membrane to drive cell energy metabolism, plays a pivotal role in WSSV infection in various crustaceans such as penaeid shrimp P . japonicus 49 and Pacific oysters Crassostrea gigas , 50 indicating that viruses can exploit VDAC. Recently, Millard et al revealed that in addition to cytoskeleton remodelling and changes in phagocytic activity that aids entry and translocation of WSSV, miRNA‐induced metabolic shifts also occur, indicating that miRNA‐induced metabolites participate in host–viral interactions 51 …”
Section: Changes In Host Metabolomementioning
confidence: 99%